ANALISIS USAHATANI TEMBAKAU (Nicotiana tabacum L) VARIETAS MAREM 1 SISTEM KEMITRAAN (Studi Kasus Di Kecamatan Pucakwangi Kabupaten Pati) - Shofia Nur Awami; Anggi Lisma Sukmawati; Sri Wahyuningsih; Dewi Hastuti (MEDIAGRO, 2023)
Tobacco is the main ingredient of the cigarette industry. Tobacco is still cultivated by farmers in several areas, as well as during the dry season. This study aims to determine the revenue, cost, income and feasibility of farming based on the value of R/C and ROI. The basic method in this study is analytical descriptive. The results of research on tobacco farming with partnership system and an average land area of 4,388 mÂ² and 8,583 mÂ² in one growing season, respectively, the average total cost incurred is IDR 6,654,690 and IDR 10,090,794. The average revenue is IDR 11,756,721 and IDR 17,595,000 so that an average income is IDR 7,348,625 and IDR 10,737,333. The R/C value in one tobacco growing season are 1.70 and 1.74 per hectare, which means that tobacco farming is feasible, and the average ROI in one growing season is 45%. This is because the ROI value is greater than the prevailing bank interest rate, which is 6% every one year or 2% every four months.